2001
DOI: 10.1093/qjmed/94.11.623
|View full text |Cite
|
Sign up to set email alerts
|

Long-term predictors of coronary artery disease and mortality in type 1 diabetes

Abstract: We assessed clinical and biochemical predictors of death and/or cardiovascular disease in 147 type 1 diabetes mellitus (DM) patients followed-up for 14 years. At follow-up, 28 of patients (19%) had died, and 25 patients (18%) had developed or died of coronary artery disease (CAD). At baseline, those who died had significantly higher serum creatinine (p=0.001) and urine albumin/creatinine ratio (p=0.016), greater prevalence of retinopathy (p=0.006), lower serum apolipoprotein A1 (p=0.046), and lower daily insul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
48
2
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 32 publications
0
48
2
2
Order By: Relevance
“…The published cumulative incidence of CHD ranges between 2.1% 18 and 19%, 19 with most studies reporting cumulative incidences of ≈15% over ≈15 years of follow-up. [20][21][22] Cumulative CHD mortality rates over 14 to 18 years are reported as being between 6% and 8%, 19,22 are higher in men than in women, 23 and are higher in those >40 years of age than in those <40 years of age 23 (online-only Data Supplement Table I). Of interest, myocarditis after myocardial infarction has been described recently in a mouse model, with some evidence that a similar complication occurs in T1DM patients.…”
Section: Coronary Heart Diseasementioning
confidence: 99%
“…The published cumulative incidence of CHD ranges between 2.1% 18 and 19%, 19 with most studies reporting cumulative incidences of ≈15% over ≈15 years of follow-up. [20][21][22] Cumulative CHD mortality rates over 14 to 18 years are reported as being between 6% and 8%, 19,22 are higher in men than in women, 23 and are higher in those >40 years of age than in those <40 years of age 23 (online-only Data Supplement Table I). Of interest, myocarditis after myocardial infarction has been described recently in a mouse model, with some evidence that a similar complication occurs in T1DM patients.…”
Section: Coronary Heart Diseasementioning
confidence: 99%
“…It is therefore possible to speculate that poor glycemic control increases all-cause mortality in type 1 diabetes predominantly by promoting progression to ESRD. Furthermore, any studies that censored ESRD patients or had few progressors may therefore have observed no mortality risk associated with HbA 1c 10,11 . For example, the lack of association between HbA 1c and mortality in the Diabetes Control and Complications Trial (DCCT) trial may be partly because of the low incidence of ESRD.…”
Section: Clinical Epidemiology Wwwjasnorgmentioning
confidence: 99%
“…elevated urinary excretion of albumin as in microalbuminuria [24] is an early indicator of kidney damage. Studies suggest that microalbuminuria defines a group at high risk of increased cardiovascular morbidity and mortality among patients with diabetes [25][26][27] or essential hypertension. [28] Moreover, microalbuminuria is associated with increased cardiovascular morbidity even in the non-diabetic, non-hypertensive population, [29] pointing out the necessity for routine screening of urinary albumin to enable prediction and prevention of future renal and cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 99%